Genetic Characterisation of Mafriwal Dairy Cattle of Malaysia Using Quantitative and Molecular Methods - Palani, Kalaiselvi (2004)
In Malaysia, there is an increasing demand for milk and other dairy products. The total milk consumption has almost doubled in the last decade, but self-sufficiency has decreased. Among the government’s effort to stimulate the dairy industry was the development of the tropicalised synthetic breed named “Mafriwal” by crossbreeding of Sahiwal and Friesian breeds. The Mafriwal, being a new breed, is still subjected to selection and improvement. Therefore, it is essential that its performance and genetic structure be monitored. This study was carried out to characterise the Mafriwal dairy cattle of Malaysia, using quantitative methods and microsatellite markers, and to investigate possible association between microsatellite markers and quantitative trait loci for milk production and reproduction traits. This study focused on the Mafriwal herd at Institut Haiwan Kluang, Johor.